HUBUNGAN PENGETAHUAN TENTANG MENOPAUSE DENGAN TINGKAT KESIAPAN MENJELANG MENOPAUSE PADA IBU PREMENOPAUSE DI DESA ROKAN KOTO RUANG - Ukhlika Mayang Sari; Fitria, Rahmi; Junita, Elvira (AHM Center, 2026)
Background:Menopause is a natural phase in a woman's life which is marked by the permanent cessation of menstruation. This phase is often accompanied by physical and psychological changes that can affect a woman's quality of life, especially if she is not well prepared. This study aims to determine the relationship between knowledge about menopause and the level of readiness for menopause in premenopausal women in Rokan Koto Ruang Village. This study uses a quantitative analytical design with a cross-sectional approach. Method:The number of samples was 40 premenopausal female respondents who were taken using the total sampling technique. The instrument used was a structured questionnaire. Data analysis was performed univariately and bivariately using the chi-square test. Results: the results showed that there was a very significant relationship between the level of knowledge and readiness to face menopause (p-value = 0.000), with an Odds Ratio (OR) of 360,000. This means that respondents with good knowledge have a 360 times greater chance of being ready to face menopause compared to those with less knowledge. Conclusion:This study concludes that good knowledge can increase women's readiness to face the menopause phase. Therefore, increasing education about menopause is very necessary, especially for premenopausal women. Keywords: Knowledge, Menopause, Readiness, Premenopause, Women